2020
DOI: 10.1016/j.diabres.2020.108295
|View full text |Cite
|
Sign up to set email alerts
|

Association of diabetes and hypertension with disease severity in covid-19 patients: A systematic literature review and exploratory meta-analysis

Abstract: The novel coronavirus infection , now a worldwide public health concern is associated with varied fatality. Patients with chronic underlying conditions like diabetes and hypertension have shown worst outcomes. The understanding of the association might be helpful in early vigilant monitoring and better management of COVID-19 patients at high risk. The aim of the meta-analysis was to assess the association of diabetes and hypertension with severity of disease.Methods: A literature search was conducted using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 17 publications
(32 reference statements)
10
69
1
9
Order By: Relevance
“…The current rapid review and meta-analysis pools the within-study adjusted measure of association and therefore strengthens the evidence emerging from the pandemic, revealing the association between diabetes and severe clinical outcomes if people with pre-existing diabetes become hospitalized due to infection with COVID-19. In agreement with emerging evidence [6,10,[64][65][66][67], we report that people hospitalized for COVID-19 with pre-existing diabetes have a 1.6 times increased risk or 2-fold increased odds of experiencing the composite outcome (mortality, admittance to ICU, requirement for IMV, clinically defined severe or critical disease). This finding strengthens the evidence of diabetes as a risk factor in patients hospitalized due to COVID-19 and their increased likelihood of developing a severe clinical course.…”
Section: Discussionsupporting
confidence: 90%
“…The current rapid review and meta-analysis pools the within-study adjusted measure of association and therefore strengthens the evidence emerging from the pandemic, revealing the association between diabetes and severe clinical outcomes if people with pre-existing diabetes become hospitalized due to infection with COVID-19. In agreement with emerging evidence [6,10,[64][65][66][67], we report that people hospitalized for COVID-19 with pre-existing diabetes have a 1.6 times increased risk or 2-fold increased odds of experiencing the composite outcome (mortality, admittance to ICU, requirement for IMV, clinically defined severe or critical disease). This finding strengthens the evidence of diabetes as a risk factor in patients hospitalized due to COVID-19 and their increased likelihood of developing a severe clinical course.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, COVID-19 was associated with increased age and heart diseases (atrial brillation). These data are in line with the current knowledge of SARS-Cov2 infection [23,24]. The lower prevalence of ACE inhibitor intake among COVID-19 seropositive patients does not support the hypothesis that these molecules could make patients more susceptible to SARS-Cov2 infection.…”
Section: Discussionsupporting
confidence: 46%
“…The knowledge, attitude, and prevention practice toward COVID-19 is an important issue because studies reported as they have to have health impact on COVID-19. [14][15][16] We had intentionally excluded children and adolescents less than 18 years and patients with a severe and uncorrectable cognitive, visual, or hearing impairment were excluded from the study as we wanted to assess the KAP of the patients and not their parents. The present study found about 68.66% of the study participants have moderate and good knowledge.…”
Section: Discussionmentioning
confidence: 99%